Effect of Sideritis leptoclada against HT-144 human malignant melanoma. Issue 6 (December 2018) - Aydoğmuş-Öztürk, Fatma; Günaydin, Keriman; Öztürk, Mehmet; Jahan, Humera; Duru, Mehmet E.; Choudhary, Muhammad I.
Abstract : Sideritis leptoclada O. Schwarz et P.H. Davis extracts were evaluated for its singlet oxygen production capacity using spectrophotometric method. The extracts producing singlet oxygen were then evaluated for cytotoxicity against malignant melanoma cancer (HT-144) and fibroblast (3T3) cell lines using the 3-[4, 5-dimethylthiazole-2-yl]-2, 5-diphenyl-tetrazolium bromide (MTT) assay. The photocytotoxicity against the HT-144 human melanoma cell line in the presence of illumination (∼≥400 nm) was also evaluated. In the standard MTT assay, the ethanol extract of S. leptoclada (100 µg/ml) showed 83.49±3.33% inhibition of HT-144 cancer cells, whereas in the illuminated MTT assay, it showed 77.46±1.97% inhibition of HT-144 cancer cells. The effects of ethanol extract on reactive oxygen species production, apoptosis, and tumor necrosis factor-α secretion were also evaluated on HT-144 cell lines. The extract triggered an increase in intracellular reactive oxygen species production and tumor necrosis factor-α secretion compared with the respective controls. Thus, the ethanol extract may cause apoptosis. The LC-MS/MS analyses of S. leptoclada ethanolic extract showed that it has quinic acid (137213±11.25 µg/g extract), malic acid (1468±0.16 µg/g extract), chlorogenic acid (881.7±0.06 µg/g extract), and apigetrin (223.2±0.13 µg/g extract) as major constituents. The ethanolic extract of S. leptoclada should be further investigated as a potential treatment for malignant melanoma cancer.